Analisis Kesesuaian dan Distribusi Level Kognitif pada Butir Soal Objektif Penilaian Sumatif Akhir Semester Bahasa Indonesia Kelas X - Hasna Arridha Hayati (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
The requirements of the Merdeka Curriculum mandate that assessments have cognitive level alignment and distribution that are consistent with Learning Outcomes (CP) and Learning Objectives (TP). This study aims to analyze the distribution of cognitive levels and their alignment with reconstruction indicators in the objective items of the End-of-Semester Summative Assessment (PSAS) for 10th-grade Indonesian Language. The study employed a descriptive qualitative approach using content analysis. The data consisted of 45 PSAS items for 10th-grade Indonesian Language, developed by the Cilacap Regency Indonesian Language Teachers’ Working Group (MGMP), and collected through documentation. The analysis was conducted by classifying the test items based on the cognitive levels of the Bloom’s Taxonomy Revised by Anderson and Krathwohl and examining their alignment with the reconstruction indicators. The validity of the data was strengthened through expert judgment by two high school Indonesian language teachers. The results of the study indicate that all test items align with the established reconstruction indicators. However, the distribution of cognitive levels did not yet show a balanced proportion. The questions were dominated by the comprehension level (C2) at 42.2%, followed by recall (C1) at 28.9% and application (C3) at 22.2%. The analysis level (C4) reached only 6.7%, while the evaluation (C5) and creation (C6) levels were not found. These findings highlight the need to develop more balanced assessments to support the attainment of higher-order thinking skills in line with the requirements of the Merdeka Curriculum.